2019
DOI: 10.1371/journal.pone.0211449
|View full text |Cite
|
Sign up to set email alerts
|

Is health related quality of life influenced by diabetic neuropathic pain among type II diabetes mellitus patients in Ethiopia?

Abstract: BackgroundPolyneuropathy is one of the commonest complications of long-standing diabetes. Progressive sensory loss can predispose patients to foot ulcer and the neuropathy oftentimes causes pain. The pain can significantly affect the quality of life of patients.ObjectivesTo describes the health-related quality of life of patients with type II diabetes mellitus suffering from painful diabetic peripheral neuropathy at two referral hospitals in Addis Ababa, Ethiopia, 2017.MethodsAn institution based cross section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 24 publications
4
35
1
2
Order By: Relevance
“…Accordingly, the prevalence ranged from 7.15% (95%CI: 3.73, 10.56) in Oromia region [12,16,17] to 19.31% (95%CI: 2.7. 41.37) in Addis Ababa [11,15,27]. The funnel plot was asymmetry, and the Egger's test also showed statistically significant publication bias (p = 0.001) at 5% significant level ( Table 2).…”
Section: Subgroup Analysismentioning
confidence: 89%
See 2 more Smart Citations
“…Accordingly, the prevalence ranged from 7.15% (95%CI: 3.73, 10.56) in Oromia region [12,16,17] to 19.31% (95%CI: 2.7. 41.37) in Addis Ababa [11,15,27]. The funnel plot was asymmetry, and the Egger's test also showed statistically significant publication bias (p = 0.001) at 5% significant level ( Table 2).…”
Section: Subgroup Analysismentioning
confidence: 89%
“…The [11] and lowest (1.36%) [27] prevalence of diabetic foot ulcer was reported in Addis Ababa (Fig. 2).…”
Section: Prevalence Of Foot Ulcermentioning
confidence: 94%
See 1 more Smart Citation
“…There is a common complication in people with diabetes that is characterized by greater sensitivity to noxious stimuli than that of normal people (hyperalgesia) [5]. Clinically, the symptoms of diabetic peripheral neuropathy seriously affect the quality of life and mental health of patients, so treating these symptoms of DPN in the clinic is a new challenge [6]. Currently, there are very few available therapies for diabetic neuropathy because therapeutic opportunities are limited by many factors, such as serious adverse reactions and ineffectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] In addition to this, similar studies conducted in different countries revealed that the burden of diabetic related chronic complications are responsible for high morbidity and mortality with significantly reduced HRQOL among type two diabetic patients in developed and low income countries. [16][17][18][19][20][21] Depression was also the major determinant factor in HRQOL with respect to physical and psychological domains in developed and low income countries. 17,21,22 In Ethiopia, diabetic related chronic complications and co-morbidity diseases have negative impact on HRQOL with respect to physical health, psychological health, social health and environmental health.…”
Section: Introductionmentioning
confidence: 99%